Pengaruh Islamic Branding dan Product Ingredients Terhadap Minat Beli Produk PT.HNI HPAI Kota Bengkulu - Nonie Afrianty; Detri Agustina (Universitas Pembangunan Nasional Veteran Jakarta, 2020)
Islamic branding as an attraction for consumers to buy. Muslim consumers are required to be selective in choosing products to consume. Halal label on product packaging does not necessarily guarantee the halal product. Some people do not see the product ingredients in buying consumer products tend to follow the Trand and the properties obtained from these products. This study aims to determine the effect of Islamic Branding and Product Ingredients Against Interest in Buying HNI-HPAI Products in Bengkulu City, the population that is the object of this research is the Consumer of HNI-HPAI Products at Al-Fatih Business Center II HPAI Bengkulu City, The samples used are as many as 94 people were sampled in this study, using the accidental sampling method. The analytical method used in this study is the multiple regression analysis method with the application of SPSS16. The results of the research are based on partial hypothesis testing (t test) showing that the Islamic Branding and Product Ingredients variables significantly influence buying interest. The results of the F test Islamic branding and product ingredients together have a positive and significant effect on buying interest. This can be seen in the calculated F value of 70.676 and a significant value of 0.000 <0.05. Determination Coefficient Test Results (R2) obtained Rsquer of 0.608. This shows that the dependent variable of buying interest can be explained by the Islamic Branding and Product Independent variables at 60.8% while 39.2% is explained by other factors outside the studied variables.